Adherend surface roughness effect on the mechanical response of silicone-based adhesive joints. (December 2020) - Zarei, Hamed; Rosaria Marulli, Maria; Paggi, Marco; Pietrogrande, Riccardo; Üffing, Christoph; Weißgraeber, Philipp
Highlights: Experimental characterization of rough adhesive joints. Peeling tests on adhesive joints with different roughness. Peeling tests by varying the adhesive thickness. Surface topography affects adhesion energy. A dimensionless number given by the adhesive thickness divided by the r.m.s. roughness plays a role for quantitative assessments. Roughness effect on damage mechanism and failure mode. Abstract: The present contribution focuses on the effect of adherend surface roughness on the strength of adhesive joints, which are particularly cost-effective and extensively applied in a wide range of industrial applications. However, the reliability of such solutions is a critical concern for the integrity of commercial products. To gain a deeper understanding on the effect of roughness, an extensive experimental campaign is proposed, where thermoplastic substrates are produced with a specified roughness, whose characterization has been performed using a confocal profilometer. Elastic strips are then bonded onto such substrates using Silicone adhesive while controlling the adhesive thickness. Peeling tests are finally carried out and the effects of joint parameters such as surface roughness, adhesive thickness, and loading rate are discussed in detail. Eventually, it is demonstrated that the surface roughness can increase the adhesion energy of joints depending on the value of a ratio between the adhesive thickness and the root mean square elevation of roughness.